Karakteristik Fisik Media Tanam dari Limbah Kerajinan Bambu dan Pelepah Aren dengan Pencampuran Cocopeat Sebagai Media Tanam Hidroponik - Dewi, Endang Purnama; Amaliah, Wenny; Saputra, Oki (Universitas Andalas, 2025)
The growing medium should have good water-holding capacity as it is essential for root growth. Roots need water to absorb nutrients and oxygen from the growing medium. Too much water can cause the roots to rot, while too little water can cause the roots to dry and die. Plants also absorb nutrients from the growing media through water. It is important to know the physical characteristics of planting media from organic waste from bamboo crafts and aren fronds as hydroponic growing media. The addition of cocopeat as a component of growing media offers a number of significant advantages, this is because cocopeat has an exceptional ability to retain water, which is essential for maintaining consistent moisture around plant roots. In addition, the porous structure of cocopeat improves aeration, allowing oxygen to reach the roots and preventing root rot. The slightly acidic to neutral pH properties of cocopeat (pH 5.0-6.8) are also ideal for most plants, creating an environment conducive to nutrient absorption. The results obtained physical characteristics of bamboo craft waste and palm fronds by adding cocopeat as a hydroponic growing medium have water content, bulk density, porosity and water holding capacity (WHC) values respectively 81.81%, 0.189 gr/cm3, 74.6%, and 450% for bamboo craft waste and 102.34%, 0.176 gr/cm3, 68.7% and 622% for palm fronds. Based on these results, it can be concluded that bamboo craft waste and palm fronds with the addition of cocopeat have high water content and are good for plant growth.